Skin prick tests and specific IgE in 10‐year‐old children: Agreement and association with allergic diseases. Issue 9 (12th April 2017) - Chauveau, A.; Dalphin, M.‐L.; Mauny, F.; Kaulek, V.; Schmausser‐Hechfellner, E.; Renz, H.; Riedler, J.; Pekkanen, J.; Karvonen, A. M.; Lauener, R.; Roduit, C.; Vuitton, D. A.; et al.
Abstract: Background: Accurate assessment of atopic sensitization is pivotal to clinical practice and research. Skin prick test (SPT) and specific IgE (sIgE) are often used interchangeably. Some studies have suggested a disagreement between these two methods, and little is known about their association with allergic diseases. The aims of our study were to evaluate agreement between SPT and sIgE, and to compare their association with allergic diseases in 10‐year‐old children. Methods: Skin prick test, sIgE measurements, and assessment of allergic diseases were performed in children aged 10 years in the Protection against Allergy: STUdy in Rural Environments (PASTURE) cohort. The agreement between SPT and sIgE was assessed by Cohen's kappa coefficient with different cutoff values. Results: Skin prick tests and sIgE were performed in 529 children. The highest agreement (κ=.44) was found with a cutoff value of 3 and 5 mm for SPT, and 3.5 IU/mL for sIgE. The area under the curve (AUC) obtained with SPT was not significantly different from that obtained with sIgE. For asthma and hay fever, SPT (cutoff value at 3 mm) had a significantly higher specificity ( P <.0001) than sIgE (cutoff value at 0.35 IU/mL) and the specificity was not different between both tests ( P =.1088). Conclusion: Skin prick test and sIgE display moderate agreement, but have a similar AUC for allergic diseases. At the cutoff value of 3 mm for SPT and 0.35 IU/mL for sIgE, SPT has a higher specificity for asthma and hay fever than sIgE without difference for sensitivity.